Study of Formaldehyde Content in Different Types of Tofu Using Micro Scale Laboratory Based Visible Beam Spectrophotometry - Atikah Atikah; Burhanuddin Ronggopuro (Program Studi Kimia, Universitas Lambung Mangkurat, 2023)
Microscale laboratory is an analytical technique that requires a little reagent and produces a little waste. One application of microscale laboratory is the analysis of formaldehyde content in tofu. Formaldehyde is one of the chemicals that is harmful to the body but is often misused as a food preservative in tofu. This study aims at determining the presence of formaldehyde in tofu using laboratory microscale-based Schiff reagents. The use of microscale laboratories is expected to reduce waste and support the implementation of green chemistry. The method used was a calibration curve using a series of standard solutions of 10 ppm, 15 ppm, 20 ppm, 25 ppm, and 30 ppm with scanning at a wavelength of 561 nm. In the qualitative test, all samples were reactive and showed a purplish red color. In the qualitative test, the highest formaldehyde content in the tofu sample was obtained in the white tofu 3 with a content of 99.7 ppm.